The Influence of Electronic Word of Mouth, Customer Relationship Management on Consumer Purchase Interest with Customer Bonding as a Mediator - Yoga, Fajri (UPI YPTK Journal of Business and Economics, 2022)
This study examines how much Electronic Word of Mouth (E-WOM) and Customer Relationship Management influence consumer purchasing interest with Customer Bonding as an intervening variable in MR. D.I.Y Marapalam Branch, Padang City. Methods of data collection through surveys and distributing questionnaires, with a sample of 100 respondents. The analytical method used is SEM analysis using smartpls3. The research results obtained based on hypothesis testing obtained that there is a significant effect of Electronic Word of Mouth on Customer Bonding. There is a significant positive influence of Customer Relationship Management on Customer Bonding. There is a significant positive effect of work motivation on Customer Bonding. There is a significant positive effect of Electronic Word of Mouth on consumer purchasing interest. Customer Relationship Management has a significant positive influence on consumer buying interest. There is a positive influence of Customer Bonding on consumer buying interest. There is a significant effect of Electronic Word of Mouth on consumer purchasing interest through Customer Bonding. Customer Relationship Management has a positive influence on consumer buying interest through Customer Bonding.